P16.10 Worsen epidemic of early hiv infection among men who have sex with men in china: implication for real time action. (13th September 2015) - Tang, W; Xu, J; Zou, H; Mahapatra, T; Hu, Q; Fu, G; Wang, Z; Lu, L; Zhuang, M; Chen, X; Fu, J; Yu, Y; et al.
Abstract : Background: Recent upsurge of new HIV infections among men who have sex with men (MSM) is a major concern in China. Paucity of national-level information regarding the burden and predictors of this progressive epidemic of new infections called for a multi-centric, timely and comprehensive investigation. Methods: Mixed methods were used to recruit MSM (MSM) from seven cities in China between 2012 and 2013. Early and established HIV infections were estimated by Western Blot and BED HIV-1 capture enzyme immunoassay. Syphilis and herpes simplex virus-2 (HSV-2) were also tested. Results: A total of 4496 eligible MSM were recruited. The majority was aged ≤35 years (77·5%), migrants (60·3%), never married (69·8%), and played receptive role in anal sex (70·5%). The HIV prevalence was 9·9%, and 41·9% were recently infected, with HIV incidence of 8·9/100 Person-Years (95% CI: 7·6–10·2). The prevalence of history HSV-2 and syphilis were 12·5% and 8·5%, respectively. Early HIV infection was associated with having multiple male partners (aOR = 1·4, 95% CI 1·1–1·9), recreational drug use (aOR = 2·2, 95% CI 1·6–3·0), anal bleeding (aOR = 2·1, 95% CI 1·4–3·0), circumcision experience (aOR = 2·0, 95% CI 1·3–3·1), syphilis infection (aOR = 2·8, 95% CI 1·9–4·3) and history HSV-2 infection (aOR = 2·3, 95% CI 1·5–3·3). Conclusion: High rate of early HIV infection is potentially resulting in progressive deterioration of the overall HIV epidemic among MSM in China. Targeted interventions to address high-risk MSM including those having multiple partners, history of recreational drug use and syphilis or HSV-2 infection seemed to be the need of the hour.